Mecanização do corte da cana-de-açúcar e desemprego: expectativas e desafios dos trabalhadores na região de catanduva/SP - Sibien, Júlia Maria [UNESP] (2014)
The alcohol and sugar sector, considered one of the most important economic activities in the State of Sao Paulo, has always involved a large contingent of labor to work in the plantations, mainly related to the cutting of sugar cane. Individuals from other states travel to the interior regions of the State to work in plants cane sugar, leaving their regions of origin. But with the onset of increased mechanization of agriculture, due to environmental protocols and reports of maltreatment in the countryside, many cutters will lose their jobs, replaced by machines, on one hand do not harm the environment, but otherwise has caused structural unemployment. This research aims to analyze what is being done to support this number of unemployed workers, what they actually intend to do after they leave their jobs, and most importantly, social expectations and labor to tackle unemployment caused by such mechanization of cutting cane sugar. For this will be used individual interviews, through interviews with workers, the literature review on the topic, and documentary analysis, with the objective to analyze the problem and achieve the desired objective.